2007 IEEE International Conference on Automation Science and Engineering 2007
DOI: 10.1109/coase.2007.4341719
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Manipulator Interactivity through Compliant Skin and Extended Kalman Filtering

Abstract: In this paper we discuss control algorithms for real-time interaction between humans and robot manipulators sharing a common workspace. Unlike traditional robotic manipulators, we assume that the interaction between human and robot is not restricted to the wrist/end-effector of the robot, but that it can happen anywhere along the kinematic chain. Interaction forces are measured in some directions, and estimated in others via an Extended Kalman Filter. Sensory measurements used are traditional shaft encoders an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The standard set of equations provided by the software has been modified to include non-default constitutive Eq. (23). A structured mesh with 2400 rectangular elements featuring Lagrange shape functions with order two is used.…”
Section: Case Study and Resultsmentioning
confidence: 99%
“…The standard set of equations provided by the software has been modified to include non-default constitutive Eq. (23). A structured mesh with 2400 rectangular elements featuring Lagrange shape functions with order two is used.…”
Section: Case Study and Resultsmentioning
confidence: 99%
“…Robots equipped with sensory skins for real time feedback are not only safer for humans, but they can also perform tasks more efficiently and successfully in unstructured and dynamically changing environments. Tactile data can be used in closed-loop feedback to implement human-guided behavior learning [1], improve safety [2], interpret human intent [3], or ensure operation in cluttered environments [4]. Useful sensory information for sensitive robotic skins include pressure, tapping, temperature, and proximity; however, the integration of different types of sensors into robotic skin is impractical due to conflicting sensing modalities, as well as incompatible materials and fabrication processes.…”
Section: Pressure Sensors For Robotic Skinsmentioning
confidence: 99%
“…It has been reported that the robot's ability to detect exterior forces can improve the communication with humans and the environment, increase the safety and facilitate the human guided behavior learning [1] [2]. This research will one-day lead to a robust and dependable human-robot interaction that is adaptable to both different users and tasks.…”
Section: Introductionmentioning
confidence: 99%